PERAN ORANG TUA DALAM MENGEMBANGKAN PERKEMBANGAN MEMBACA ANAK USIA 5-6 TAHUN DI PAUD B SPS DAARUSSHOLIHIN - Rosihah (LPPM Universitas Muhammadiyah Cirebon, 2025)
this study aims to describe the role of parents in developing the reading ability of children aged 5–6 years at PAUD B SPS Daarussholihin, Cilegon City. The research employed a qualitative descriptive approach. The subjects consisted of five parents and five children from group B aged 5–6 years. Data were collected through in-depth interviews, observations, and documentation, and analyzed through data reduction, categorization, and interpretation stages. The findings revealed that active parental involvement has a significant impact on early literacy development. The most prominent forms of parental roles include reading bedtime stories, guiding children to recognize letters and words, and providing positive motivation during reading activities. Supporting factors in literacy development include parents’ awareness of early reading importance, joint reading habits, and active communication with teachers. Meanwhile, inhibiting factors include limited parental time, children’s preference for gadgets, and lack of reading material variety at home. Overall, the study concludes that parental involvement serves as a crucial foundation in fostering reading interest and ability among early childhood learners. Keywords: parental role, reading ability, early childhood, family literacy, parental involvement